2004
DOI: 10.1074/jbc.m405346200
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Production of a Peroxisome Proliferator-activated Receptor-γ Ligand during an Early Phase of Adipocyte Differentiation in 3T3-L1 Adipocytes

Abstract: Peroxisome proliferator-activated receptor-␥ (PPAR␥) is a nuclear hormone receptor that is critical for adipogenesis and insulin sensitivity. Ligands for PPAR␥ include some polyunsaturated fatty acids and prostanoids and the synthetic high affinity antidiabetic agents thiazolidinediones. However, the identity of a biologically relevant endogenous PPAR␥ ligand is unknown, and limited insight exists into the factors that may regulate production of endogenous PPAR␥ ligands during adipocyte development. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 57 publications
2
158
0
1
Order By: Relevance
“…At the early stage, at least one PPARÁ agonist is synthesized to induce 3T3-L1 adipocyte differentiation (20). In our study, we found that clonal expansion is not necessary for adipocyte differentiation when lecithin is used as the inducer, since the proliferation of 3T3-L1 preadipocytes was inhibited by lecithin, indicating the adipocyte differentiation induced by lecithin is independent of the clonal expansion.…”
Section: Discussionmentioning
confidence: 50%
“…At the early stage, at least one PPARÁ agonist is synthesized to induce 3T3-L1 adipocyte differentiation (20). In our study, we found that clonal expansion is not necessary for adipocyte differentiation when lecithin is used as the inducer, since the proliferation of 3T3-L1 preadipocytes was inhibited by lecithin, indicating the adipocyte differentiation induced by lecithin is independent of the clonal expansion.…”
Section: Discussionmentioning
confidence: 50%
“…Other studies have revealed that an endogenous PPARg ligand is generated during an early phase of the adipogenic process in 3T3-L1 cells. 23 This suggests a hypothesis that some factors released during adipogenesis, particularly as a result of MCE, are essential for the transition of the cells into terminal differentiation. In this study, we have shown that CM accelerates differentiation into mature adipocytes, suggesting that additional events are required for the transition into terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 15d-PGJ 2 can drive PPAR␥-derived adipocyte differentiation but only at concentrations considerably in excess of those formed endogenously (24,32). Other compounds formed naturally also possess the capacity to activate PPAR␥; among them are 9-HODE, 13-HODE, and 15-hydroxyeicosatetraenoic acid (10,16), lysophosphatidic acid (17), and nitrolinoleic acid (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that treatment of 3T3-L1 preadipocytes with dexamethasone and insulin (DI) is unable to induce adipocyte differentiation unless methylisobutylxanthine (MIX) is added to DI to stimulate the generation of endogenous PPAR␥ ligands via the cAMP signaling pathways (31,32). This system allows us to evaluate the effect of supplementation of PPAR␥ ligands on the promotion of adipogenesis in the absence of methylisobutylxanthine.…”
Section: -Keto-pge 2 Activates Ppar␥-mediated Transcription and Enhmentioning
confidence: 99%